KARAKTERISTIK LITHIUM-POLYMER BATTERY UNTUK APLIKASI RADIO YANG DI GUNAKAN PERSONIL TNI DALAM MENDUKUNG IKN LITERATURE REVIEW - Florianus Lamablawa; Sovian Aritonang (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
A battery is an electrochemical cell that converts chemical energy into electrical energy. Lithium Polymer (Li-Po) Batteries are Almost the same as Li-Ion batteries, but Li-Po batteries do not use the liquid as an electrolyte but instead a dry polymer electrolyte shaped like a thin film of plastic. This film layer is arranged in layers between the anode and cathode, resulting in ion exchange. Radio is electromagnetic signal radiation that propagates through the atmosphere and a vacuum. The wave components modulate information sent via electromagnetic waves, namely amplitude, frequency, phase, or pulse width. The radiation is formed when an audio wave modulates an electrically charged object from a carrier wave at a radio frequency on an electromagnetic spectrum. The Capital of the Archipelago (IKN) is a planned city that will replace Jakarta as the capital city of Indonesia starting in 2024. TNI personnel can use the Radio application as a communication tool to maintain security in supporting IKN.